Pemanfaatan Recorder Sebagai Media Pembelajaran Dalam Pembelajaran Tembang Dolanan Bahsa Jawa Di Sekolah Dasar - Zahro, Anisa; Su’adah, Muthorida; Wijayanto, Wasis (Universitas Asahan, 2025)
This study aims to describe the implementation of the recorder musical instrument as a learning medium in teaching Javanese traditional children's songs (tembang dolanan) in elementary schools, and to analyze its impact on students’ understanding. A qualitative descriptive method was employed, using a case study approach at Grade I of SD 3 Adiwarno. Data collection techniques included observation and documentation, with data analyzed using the Miles and Huberman interactive model. The findings reveal that the use of recorder media enhances students' active participation, helps them follow rhythmic patterns, sing traditional songs correctly, and understand the vocabulary and meaning of Javanese lyrics. The learning atmosphere became more enjoyable, interactive, and contextual. Thus, the recorder serves not only as a teaching aid but also as an effective medium for preserving local culture through tembang dolanan.